Systemsof3 equations ppt_alg2

253 views

Published on

Published in: Technology
0 Comments
0 Likes
Statistics
Notes
  • Be the first to comment

  • Be the first to like this

No Downloads
Views
Total views
253
On SlideShare
0
From Embeds
0
Number of Embeds
4
Actions
Shares
0
Downloads
4
Comments
0
Likes
0
Embeds 0
No embeds

No notes for slide

Systemsof3 equations ppt_alg2

  1. 1. Solving Systems of Three Linear Equations in Three Variables The Elimination Method LEQ      How to solve systems of three linear equations in three variables?
  2. 2. Solutions of a system with 3 equations The solution to a system of three linear equations in three variables is an ordered triple. (x, y, z) The solution must be a solution of all 3 equations.
  3. 3. Is (–3, 2, 4) a solution of this system? 3x + 2y + 4z = 11 2x – y + 3z = 4 5x – 3y + 5z = –1 3(–3) + 2(2) + 4(4) = 11 2(–3) – 2 + 3(4)  = 4 5(–3) – 3(2)  + 5(4)  = –1    Yes, it is a solution to the system because it is a solution to all 3 equations.
  4. 4. Methods Used to Solve Systems in 3 Variables 1. Substitution 2. Elimination 3.  Cramer’s Rule 4.  Gauss-Jordan Method …..  And others
  5. 5. Why not graphing? While graphing may technically be used as a means to solve a system of three linear equations in three variables, it is very tedious and very difficult to find an accurate solution. The graph of a linear equation in three variables is a plane.
  6. 6. This lesson will focus on the Elimination Method.
  7. 7. Use elimination to solve the following system of equations. x – 3y + 6z = 21 3x + 2y – 5z = –30 2x – 5y + 2z = –6
  8. 8. Step 1 Rewrite the system as two smaller systems, each containing two of the three equations.
  9. 9. x – 3y + 6z = 21 3x + 2y – 5z = –30 2x – 5y + 2z = –6 x – 3y + 6z = 21 x – 3y + 6z = 21 3x + 2y – 5z = –30 2x – 5y + 2z = –6
  10. 10. Step 2 Eliminate THE SAME variable in each of the two smaller systems. Any variable will work, but sometimes one may be a bit easier to eliminate. I choose x for this system.
  11. 11. (x – 3y + 6z = 21) 3x + 2y – 5z = –30 –3x + 9y – 18z = –63 3x + 2y – 5z = –30 11y – 23z = –93 (x – 3y + 6z = 21) 2x – 5y + 2z = –6 –2x + 6y – 12z = –42 2x – 5y + 2z = –6 y – 10z = –48 (–3) (–2)
  12. 12. Step 3 Write the resulting equations in two variables together as a system of equations. Solve the system for the two remaining variables.
  13. 13. 11y – 23z = –93 y – 10z = –48 11y – 23z = –93 –11y + 110z = 528 87z = 435 z = 5 y – 10(5) = –48 y – 50 = –48 y = 2 (–11)
  14. 14. Step 4 Substitute the value of the variables from the system of two equations in one of the ORIGINAL equations with three variables.
  15. 15. x – 3y + 6z = 21 3x + 2y – 5z = –30 2x – 5y + 2z = –6 I choose the first equation. x – 3(2) + 6(5) = 21 x – 6 + 30 = 21 x + 24 = 21 x = –3
  16. 16. Step 5 CHECK the solution in ALL 3 of the original equations. Write the solution as an ordered triple.
  17. 17. x – 3y + 6z = 21 3x + 2y – 5z = –30 2x – 5y + 2z = –6 –3 – 3(2) + 6(5) = 21 3(–3) + 2(2) – 5(5) = –30 2(–3) – 5(2) + 2(5) = –6    The solution is (–3, 2, 5).
  18. 18. is very helpful to neatly organize you k on your paper in the following mann (x, y, z)
  19. 19. Try this one. x – 6y – 2z = –8 –x + 5y + 3z = 2 3x – 2y – 4z = 18 (4, 3, –3)
  20. 20. Here’s another one to try. –5x + 3y + z = –15 10x + 2y + 8z = 18 15x + 5y + 7z = 9 (1, –4, 2)

×